Operationalizing Maqāṣid al-Sharī‘ah for Sustainable MSME Development: A Comparative Study of Fresh Maggot Farming and Pellet Feed Diversification in Indonesia - Dewi Kumalasari; Muhammad Ahmad Fulka Sa'dibih; Alimatul Farida; Beny Arihakam (IQTISHODUNA: Jurnal Ekonomi Islam, 2026)
This study analyzes the financial performance and sustainability implications of fresh maggot farming and diversification into animal feed pellets among micro-scale enterprises in Mojokerto, Indonesia. The study addresses the limited integration of maqāṣid al-sharī‘ah in agribusiness sustainability analysis by linking Islamic sustainability dimensions with measurable business indicators. A qualitative case study approach was employed through in-depth interviews, observation, financial documentation, and comparative financial analysis. Business performance was assessed using Return on Investment (ROI), Revenue-Cost Ratio, and payback period, while sustainability was evaluated through maqāṣid-based indicators: hifz al-mal (profitability stability), hifz al-bi’ah (waste reduction), and maslahah (stakeholder benefit). The findings reveal that fresh maggot farming generates higher ROI because of lower operational costs, whereas pellet diversification provides greater nominal profit, product durability, and long-term income stability. The study contributes to Islamic economics literature by operationalizing maqāṣid al-sharī‘ah into measurable sustainability indicators for MSME-based agribusiness development and sustainable business decision-making.